Performance of lightweight concrete with silica fume after high temperature - Tanyildizi, Harun; Coskun, Ahmet (Elsevier Sci Ltd, 2008)
In this study, the effect of silica fume on compressive and splitting tensile strength of lightweight concrete after high temperature was investigated experimentally and statistically. The mixes incorporating 0%, 10%, 20% and 30% silica fumes were prepared. After being heated to temperatures of 200, 400 and 800 degrees C, respectively, the compressive and splitting tensile strength of lightweight concrete was tested. This article adopts Taguchi approach with an L-16 (4(5)) to reduce the numbers of experiment. Two control factors (percentage of silica fume and heating degree) for this study were used. The level of importance of these parameters on compressive and splitting tensile strength was determined by using analysis of variance (ANOVA) method. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: lightweight concrete; silica fume; high temperature; mechanical properties; analysis of variance (ANOVA)